Marine Gastropod and Bivalves of Sampadi Island, Lundu, Sarawak - Shabdin, Mohd Long; Abg Azizil, Fansuri Abg Abdullah; Syahidatul Atiqah, Ab Rahim (2014)
Sampadi Island is located close to Satang Islands National Park, Sarawak. Information on the molluscs community in Sampadi Island is still lacking. The initiative of doing the study in Sampadi Island is carried out due to the proposal of the area to be gazetted as part of the Talang-Satang Island National Park. The objectives of this study were to determine the gastropods and bivalves community structure in Sampadi Island. The study focused on species composition, species diversity and distribution of gastropod and bivalves around the Sampadi Island. The approach taken were by performing the line transect running from high to low tide levels at three selected stations on the intertidal area of the island. The animal species that present in the transect were counted and identified. Thirty-three species of gastropods and seven species of bivalves are recorded from Sampadi Island. The species diversity of both molluscs class is low due to (some) dominant species presence in the samples. The molluscs species found in rocky shore are higher than seagrass meadows due to larger sampling area. The Sampadi Island was found to be habitable to a number of gastropod and bivalves species in their surrounding waters. This baseline data is useful as one of the biological component in proposing the area to be gazetted as part of the Talang-Satang Island National Park in the future.